Improving Students’ Writing Ability through Small Group Discussion Technique - Lara Septia; Eva Nurchurifiani; Sri Wahyuningsih (CV. Tripe Konsultan, 2022)
This research aimed to improve students’ writing ability by using Small Group Discussion Technique. The subject of this research was the 8th B Grade of SMP Negeri 9 Bandar Lampung. It consisted of 30 students. This research used Classroom Action Research (CAR) method which was consisted of 2 cycles. In this research, the writer used test and non-test in collecting data. The test used in the research was formative and summative test. Meanwhile in non-test, the writer used field note and observation sheet. In analyzing data, this research used quantitative and qualitative data. Based on the result of the research, it found that there was an improvement in students’ writing ability after implementing Small Group Discussion. Refers to the result of the test, it showed that a number of students who get the score ≥75 is about 17 students with the percentage 56.70% in the first cycle. Meanwhile, it was better in the second cycle. In this cycle, a number of students who get the score ≥75 is about 22 students with percentage 73.30%. in the other hand, referring to the students’ attitude or behaviour to the lesson. It showed that there were some positive progression that supported them in mastering the lesson. Therefore, it can be concluded that the implementation of Small Group Discussion is successful to improve students’ writing ability at the Eighth grade of SMP Negeri 9 Bandar Lampung.